The Effect of Group Schema Therapy on marital adjustment and marital Intimacy in Couples in Kerman - Shifteh Shahabi; Gholamreza Sanagouye-Moharer (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Schema therapy is one of the effective therapies in the field of marital relationships, such as marital adjustment and Intimacy. The purpose of the present study was to determine the effectiveness of group schema therapy on the marital adjustment and marital intimacy of couples in Kerman. Materials and Methods: This research was semi experimental and with pre-test and post-test design with control group. The target population included all couples referring to counseling centers in Kerman. A relative class method was used to select the sample. So, 60 (30 couples) were selected and randomly divided into two experimental and control groups (each containing 30 people). The research tools included marital intimacy scale and Dyadic Adjustment Scale (DAS). To analyze the data, multivariate covariance analysis were used by Spss.22. Results: The mean (standard deviation) of the participants was 39.5 (6.1), which included the age range of 29 to 53 years. The results of this study showed that the marital adjustment score in the pre-test of the experimental group was (6.5) 83.2 to (9.1) 96.2 in the post-test (P<0.001), and the marital intimacy score was (4.2) 15.8 In the pre-test, it increased to (4.2) 21.1 in the post-test (P<0.001). Increasing the participants' scores in both of the studied variables was higher in the experimental group than in the control group. Conclusion: It can be concluded that the schema therapy approach can improve marital intimacy and marital adjustment of couples. DOI: http://doi.org/10.22037/ch.v6i3.22565